Intention and Investment Selections in Amanah Saham Bumiputera (ASB): Evidence from Kelantan - Zahri, Fatin ‘Alia; Zahri, Mohd ‘Adli; Radin Badaruddin, Radin Firdaus; Hamat, Zahri; Muhd Adnan, Nurul Ilyana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study investigates the impact of intrinsic, extrinsic, and religiosity factors on investment selections in Amanah Saham Bumiputera (ASB) among investors in Kelantan, focusing on the mediating role of intention. A survey was conducted with 300 ASB investors, and data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that extrinsic factors, such as marketing, and religiosity significantly influence ASB investment selections, with intention acting as a mediator. In contrast, intrinsic factors, such as the understanding of ASB, exhibit a weaker relationship with investment selections. The findings underscore the importance of offering Shariah-compliant investment products to meet the religious needs of investors. Additionally, enhancing financial education is vital to ensuring that investment choices align with ethical and social responsibility standards. Stakeholders are encouraged to collaborate with religious bodies to develop Shariah-aligned policies, thereby enhancing the acceptance and effectiveness of investment products in Kelantan.